Improvements to a sailing VR simulator environment for assessing and improving helm performance - Spenkuch, T.; Turnock, S.; Scarponi, M.; Shenoi, A. (The Engineering of sport 7, Volume 2, 2008)
The sailing Simulator 'Robo-Race' is used to examine the effect on sailor performance of enhancing the realism of the Simulation. For this purpose, the following two human interface device/display environments were evaluated. Firstly, a Basic Display Environment (BDE) which consists of two screens in conjunction with a Joystick. Secondly the Advanced Display Environment (ADE) that consists of three projectors with an additional screen and a steering (or helm) wheel as interface device. A number of sailors who were divided according to their sailing skills and their experience with Computer game interface devices had to deal with seven upwind races against two Computer controlled America's Cup Class (ACC) yachts. The experiment shows that the combination of BDE/joystick limits their natural sailing behaviour. However, the combination of ADE/steering wheel significantly improved the sailors' efficiency. The ADE setup has been shown to enhance the realism of the Simulation and allowed the sailors' to race opponents in a more realistic manner.